KONFLIK BATIN ZENCHI NAIGU DALAM CERPEN HANA KARYA AKUTAGAWA RYUUNOSUKE - Irene Alim Yuwono; Sri Oemiati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
Conflict is one thing we usually experience in our lives. This can be internal or external one. Â Â This study is aimed at describing the internal conflict experienced by Zenchi Naigu. The source of data is Akutagawa RyÅ«nosukeâ€™sÂ  short story entitled â€œHanaâ€ (Nose). This conflict is analyzed using personality theory proposed by Freud,Â  which includes Id, Ego, and Superego. In this theory, it is said that there is a conflict between Id and Superego which is caused by the unstable (weak) function of Ego.Â  The steps to analyze the data are reading the short story, analyzing the conflict and interpreting the finding. The result showed that Zenchi Naigu experienced that conflict because of his desire to shorten his nose. Finally he realized that his desire is against his destiny. Â  Keywords: Psychoanalysis, internal conflict, id, ego, superego.